Acute pancreatitis-induced by platinum compounds in patients with cancer: a review of the literature - Nashwan, Abdulqadir J.; Yassin, Mohamed A.; Nair, Sindhumole L. (International Journal of Basic & Clinical Pharmacology, 2017)
The purpose of this review of the literature was to describe the relationship between use of platinum-based antineoplastics and development of acute pancreatitis in patients with cancer. A literature search was conducted using PubMed, Science Direct and Google scholar databases for articles published from 1985 to 2014. The headings and/or text words (platinum compounds), (acute pancreatitis-induced by platinum compounds), and (cisplatin, carboplatin, and oxaliplatin) were entered, and the search was limited to articles describing case reports in adults with cancer. A total of 12 cases were reported between 1985 and 2012; including three platinum compounds; cisplatin, carboplatin, and oxaliplatin. In conclusion, it is highly recommended to include baseline assessment for acute pancreatitis risk factors and to consider acute pancreatitis in the differential diagnosis of abdominal pain in patients who have received platinum-based chemotherapy.